ANTIBACTERIAL EFFECT PROPOLIS AGAINST ESCHERICHIA COLI AND SHIGELLA DYSENTERIAE IN VITRO - Ferdi, Roni; Saleh, Irsan; Theodorus, Theodorus; Salni, Salni (Biomedical Journal of Indonesia, 2019)
The bacteria that often cause infectious diarrhea are Escherichia coli and Shigella dysenteriae. Excessive and less rational use of antibiotics in diarrhea cases encourages the development of multi drug pathogen resistance. Propolis is one solution to overcome diarrheal infections. The purpose of this study was to determine the ability of the antibacterial effects of propolis extract on Escherichia coli and Shigella dysenteriae bacteria in in vitro testing with various concentrations. Research in laboratory experiments in vitro. The sample in this study was the bacteria Escherichia coli and Shigella dysenteriae with the stages of research starting from the extraction process carried out using a multilevel extraction method. The results showed that the smallest concentration of n-hexane fraction which still inhibited the growth of Escherichia coli and Shigella dysenteriae bacteria was 250 µg / ml and this concentration was expressed as KHM value. The equality test of 250 µg / ml n-hexane propolis fraction was equivalent to 4.0 µg / ml ciprofloxacin to Escherichia coli and equivalent to 4.6 µg / ml ciprofloxacin against Shigella dysenteriae, while the equality test concentration of 250 µg / ml ethyl acetate propolis equivalent to 5.2 µg / ml of ciprofloxacin against Escherichia coli and equivalent to 4.5 µg / ml of ciprofloxacin against Shigella dysenteriae. The conclusion of this study is that n-hexane extract and ethyl acetate propolis have antibacterial effectiveness against Escherichia coli and Shigella dysenteriae. The n-hexane and ethyl acetate propolis fractions have lower antibacterial activity compared to ciprofloxacin in inhibiting the growth of Escherichia coli and Shigella dysenteriae. Antibacterial compounds contained in the n-hexane fraction and ethyl acetate propolis are flavonoids and phenol